KEANEKARAGAMAN JENIS BURUNG DIURNAL DI PERKEBUNAN KELAPA SAWIT PTPN XIII (Persero) DESA AMBOYO INTI KECAMATAN NGABANG KABUPATEN LANDAK - Simanjuntak, Erick Jeksen; Nurdjali, Bachrun; Siahaan, Sarma (Universitas Tanjungpura, 2013)
Birds (Avifauna) is one species were badly affected to presence of forest land use change, especially in plantations with similar vegetation (monokultur) such as oil palm plantations. The purpose and benefits of this research are to find out how much diversity of bird species diurnal in Palm oil Plantation PTPN XIII (Persero) Amboyo Inti village Ngabang Subdistrict Landak Regency. Based on the results of observations show that of the three habitats in the observation path, obtained the number of diurnal birds have been found in the study sites 17 types, are classified into 10 families namely : (Rallidae), (Cuculidae), (Piosidae), (Sylvilidae), (Turnidaei), (Pycnonotidae), (Picidae), (Accipitiridae), (collumbidae), (necttaindae). In the secondary forest habitat found 13 species of diurnal birds, habitat for palm plantations 12 species and 9 species in settlements. From the calculation, Highest dominance index contained in Settlements habitat, morning, C = 0.17409, noontime C = 0.17868, and afternoon C = 0.17086. Whereas the highest species diversity index contained in Secondary forest habitat with the value of morning H = 1,01482, noontime H = 0,99372, afternoon H = 0,94602 and the Oil Palm Plantation habitat have a high diversity index values in the afternoon with value H =0,94095. Habitat differences provide a clear influence of the dominant species, where this species dominance is the opposite of diversity. Small species diversity produces great mastery of habitat, so that species dominance will spread more evenly because with the least number of species possible number of individuals to live and develop better. Keyword : Species diversity, Bird diurnal, palm oil, plantation, PTPN XIII (Persero).